1979
DOI: 10.1152/jappl.1979.47.6.1194
|View full text |Cite
|
Sign up to set email alerts
|

Influence of air velocity and heat acclimation on human skin wettedness and sweating efficiency

Abstract: Before and after heat acclimation, four male resting subjects were exposed to humid heat that caused levels of skin wettedness ranging from 50 to 100%. The physical experimental conditions were chosen so that the same skin wettedness was attained with modification of only the ambient water vapor pressure, at two wind speeds (0.6 and 0.9 m . s-1). The esophageal temperature (Tes), mean skin temperature (Tsk), sweating rate (msw), and dripping sweat rate (mdr) were recorded; the amounts of local drippage in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 0 publications
1
46
1
2
Order By: Relevance
“…This finding is corroborated by some (Candas et al, 1979b, Rowell et al, 1967 but not by others. (Patterson et al, 2004;Mitchell et al, 1976;Kenney et al, 1990).…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations
“…This finding is corroborated by some (Candas et al, 1979b, Rowell et al, 1967 but not by others. (Patterson et al, 2004;Mitchell et al, 1976;Kenney et al, 1990).…”
Section: Discussionsupporting
confidence: 49%
“…Increased Ṁ sw is partly responsible for the higher w sk and E sw also observed, (Mitchell et al, 1976;Candas et al, 1979b); however, as shown by others (Mitchell et al, 1976), Ṁ sw was also related to an increase in the nonevaporated sweat. Belding and Hatch (1955) have stated that nonevaporated sweat should not be considered physiologically inefficient, because oversweating is necessary to satisfy the w sk requirements, which, in turn, has been found to be responsible for the higher E sw (Berglund and Gonzalez, 1977).…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…additional air flow does not improve the evaporative efficiency of sweat ( sw )). Seminal work by Candas (1979aCandas ( , 1979b and others (Givoni, 1963;Kerslake, 1963) demonstrated that as E req approaches E max , an exponential reduction in  sw occurs, that is, progressively more sweat drips off the body and does not contribute to evaporative heat loss from the skin. With electric fan use, the additional air flow increases the evaporative heat transfer coefficient (h e ), and subsequently increases E max.…”
Section: The Us Environmental Protection Agency (Epa) Seems To Provmentioning
confidence: 99%